Remix video and the crisis of the humanities. - Middleton, Kim (Transformative Works & Cultures, 2012)
The discourses of crisis in the humanities is juxtaposed with an analysis of remix video practices to suggest that the cognitive and cultural engagement feared lost in the former appear with frequency and enthusiasm in the latter. Whether humanists focus on the deleterious effects of the digital or celebrate the digital humanities but resist a turn to computation, their anxieties turn to the disappearance of textual analysis, aesthetics, critique, and self-reflection. Remix video, as exemplified by mashups, trailer remixes, and vids, depends on these same competencies for the creation and circulation of its works. Remix video is not the answer to the crises of the humanities; rather, the recognition of a common set of practices, skills, and values underpinning scholars and video practitioners' work provides the basis for a coalitional approach: identification of shared opportunities to promote and engage potential participants in the modes of thinking and production that contend with complex cultural ideas.